Трансформация этнической идентичности в Украине (Киев, Крым, 2005-2011 гг.) - Снежкова, И. (Матеріали до української етнології, 2011)
В статье, написанной на материалах социологических исследований и опроса украинской молодежи Киева и Симферополя, анализируются проблемы этнического самосознания и идентичности, рассматриваются вопросы межэтнической толерантности. In the article, which was written on materials of sociological research and public opinion polls of Ukrainian youth living in Kyiv and Simferopol, issues of ethnic self-consciousness and identity are being analyzed, and interethnic tolerance is also being examined.